2007
DOI: 10.1007/s10585-007-9095-5
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion molecules and chemokines: the navigation system for circulating tumor (stem) cells to metastasize in an organ-specific manner

Abstract: To date, cancer is still the second most prevalent cause of death after cardiovascular diseases in the industrialized word, whereby the primary cause of cancer is not attributed to primary tumor formation, but rather to the growth of metastases at distant organ sites. For several years it was considered that the well-known phenomenon of organ-specific spreading of tumor cells is mostly a mechanical process either directed passively due to size constraints (mechanical trapping theory) or due to a fertile enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 214 publications
(368 reference statements)
1
66
0
2
Order By: Relevance
“…We have recently demonstrated that hybrid cells, which derived from spontaneous fusion events between a human breast epithelial cell line and a human breast cancer cell line, but not the parental cells, responded to the chemokine CCL21 with an increased migratory activity 26 . CCL21 has been associated with lymph node metastasis formation of various cancer types, including breast 38 , suggesting that cell fusion could be a process how tumor (hybrid) cells could acquire metastatic properties 39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…We have recently demonstrated that hybrid cells, which derived from spontaneous fusion events between a human breast epithelial cell line and a human breast cancer cell line, but not the parental cells, responded to the chemokine CCL21 with an increased migratory activity 26 . CCL21 has been associated with lymph node metastasis formation of various cancer types, including breast 38 , suggesting that cell fusion could be a process how tumor (hybrid) cells could acquire metastatic properties 39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…The Arg-Gly-Asp motif present in the lunasin structure is a recognition site for integrin receptors present in the extracellular matrix (ECM). Integrins are heterodimeric receptors associated with cell adhesion, and cancer metastasis [62]. Treatment of KM12L4 cells with lunasin resulted in the modification on the expression of 62 genes associated with ECM and cell adhesion [59].…”
Section: Lunasin Against Colon Cancer In Vitromentioning
confidence: 99%
“…Chemokines are chemoattractant molecules that regulate cellular trafficking (1)(2)(3)(4). Secretion of chemokines by tumor cells has been correlated with angiogenesis, tumor growth and metastasis in a variety of experimental and human tumors (reviewed in refs.…”
Section: Introductionmentioning
confidence: 99%
“…Secretion of chemokines by tumor cells has been correlated with angiogenesis, tumor growth and metastasis in a variety of experimental and human tumors (reviewed in refs. 1,5). The organotropism of cancer metastasis is believed to occur, at least in part, through secretion of chemokines by distant organs/tissues that direct the migration of tumor cells that come into proximity to the tissue (1,5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation